Seed germination index of two varieties of papaya (Carica papaya L.) under the Bioplant substrate / Índice de germinação de sementes de duas variedades de mamão (Carica papaya L.) em substrato Bioplant - Luan Lucas Cardoso Lima; Diego Jorge da Silva; Luiz Eduardo Bezerra Silva; Rubens Pessoa de Barros (Universidade Estadual de Alagoas, 2018)
In Brazilian commercial plantations, one form of propagation most used for papaya is the use of seed, since it is a better way of propagation. This work objected to evaluate the seed germination index of two varieties of papaya (Carica papaya L.) on the Bioplant® substrate, which are the Havaí and papaya Formosa varieties, evidencing which variety was a significant increase in germination and the most efficient development in the seedling performance. Seed sowing occurred in Styrofoam trays containing 200 cells, being used for each variety 20 cells, seeded 3 seeds each under the Bioplant® substrate. The seeds of papaya Formosa showed greater adaptation under the substrate Bioplant®, being its germination index greater than the papaya Havaí and showing more vigor in the conditions that both were submitted. In this way, the Papaya Formosa showed better response the conditions provided by the substrate Bioplante in relation to the Havaí papaya.